2006
DOI: 10.1099/ijs.0.64452-0
|View full text |Cite
|
Sign up to set email alerts
|

Metschnikowia orientalis sp. nov., an Australasian yeast from nitidulid beetles

Abstract: A novel species, Metschnikowia orientalis sp. nov., is described for haploid, heterothallic yeasts isolated from nitidulid beetles sampled in flowers in Rarotonga in the Cook Islands, and the Cameron Highlands of Malaysia. As evidenced by analysis of D1/D2 large subunit rDNA sequences, the species is related to Candida hawaiiana, to which it is similar in growth responses. Cylindrical, conjugated asci and acicular ascospores of moderate size are formed. Rudimentary mating reactions were observed with Metschnik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Another interesting case is a subclade typified by Metschnikowia arizonensis (Lachance & Fedor, 2014), represented by six described and undescribed species restricted to specific locations, sometimes to a single locality, in the USA, Costa Rica, Brazil or Belize, mainly in association with species of nitidulids of the genera Carpophilus and Conotelus. Other Metschnikowia species associated with flowers and beetles, but not included in the large-spored clade, also have distinct ecologies and restricted geographical distributions, for example Metschnikowia corniflorae, associated with chrysomelid beetles and flowers in the USA (Nguyen et al, 2006), Metschnikowia orientalis, isolated from nitidulid beetles in the Cook Islands and Malaysia (Lachance et al, 2006b), and Candida chrysomelidarum, found in Panama in chrysomelid beetles (Nguyen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting case is a subclade typified by Metschnikowia arizonensis (Lachance & Fedor, 2014), represented by six described and undescribed species restricted to specific locations, sometimes to a single locality, in the USA, Costa Rica, Brazil or Belize, mainly in association with species of nitidulids of the genera Carpophilus and Conotelus. Other Metschnikowia species associated with flowers and beetles, but not included in the large-spored clade, also have distinct ecologies and restricted geographical distributions, for example Metschnikowia corniflorae, associated with chrysomelid beetles and flowers in the USA (Nguyen et al, 2006), Metschnikowia orientalis, isolated from nitidulid beetles in the Cook Islands and Malaysia (Lachance et al, 2006b), and Candida chrysomelidarum, found in Panama in chrysomelid beetles (Nguyen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…and Ipomoea indica flowers. The collection sites were located at an altitude of approximately 1500 m in the Cameron Highlands (4 u 309 N 101 u 249 E), where the climate is cool and humid year round with a temperature range of 14-23 u C (Lachance et al, 2006). Insects were collected in sterile plastic bags and later allowed to walk on the surface of YMA plates.…”
mentioning
confidence: 99%
“…The novel anamorphic species (including strains CBS 8534, CBS 8533 T , CBS 8580 T , CBS 8584 T , CBS 8586 T ) were, therefore, described as being part of the Metschnikowia/Clavispora clade until additional differential characteristics can be identified that might distinguish species within this clade from one another. Lachance et al (2006) argued against the subdivision of Metschnikowia into smaller genera on the basis of rRNA gene sequence data, as suggested by Mendonça-Hagler et al (1993), due to their highly divergent nature and the fact that some form of mating reaction was observed between species in this clade. Finding teleomorphic stages of the anamorphic species within this clade may also widen our understanding of the biological relationships that exist among species within this highly divergent clade.…”
Section: Sequence Comparisonmentioning
confidence: 97%